Phylogenetic impoverishment of Amazonian tree communities in an experimentally fragmented forest landscape - Santos, Bráulio Almeida; Tabarelli, Marcelo; Melo, F. P.L.; Camargo, José Luís Campana; Andrade, Ana C.S.; Laurance, Susan G.W.; Laurance, William F. (PLoS ONE, 2014)
Amazonian rainforests sustain some of the richest tree communities on Earth, but their ecological and evolutionary responses to human threats remain poorly known. We used one of the largest experimental datasets currently available on tree dynamics in fragmented tropical forests and a recent phylogeny of angiosperms to test whether tree communities have lost phylogenetic diversity since their isolation about two decades previously. Our findings revealed an overall trend toward phylogenetic impoverishment across the experimentally fragmented landscape, irrespective of whether tree communities were in 1-ha, 10-ha, or 100-ha forest fragments, near forest edges, or in continuous forest. The magnitude of the phylogenetic diversity loss was low (<2% relative to before-fragmentation values) but widespread throughout the study landscape, occurring in 32 of 40 1-ha plots. Consistent with this loss in phylogenetic diversity, we observed a significant decrease of 50% in phylogenetic dispersion since forest isolation, irrespective of plot location. Analyses based on tree genera that have significantly increased (28 genera) or declined (31 genera) in abundance and basal area in the landscape revealed that increasing genera are more phylogenetically related than decreasing ones. Also, the loss of phylogenetic diversity was greater in tree communities where increasing genera proliferated and decreasing genera reduced their importance values, suggesting that this taxonomic replacement is partially underlying the phylogenetic impoverishment at the landscape scale. This finding has clear implications for the current debate about the role human-modified landscapes play in sustaining biodiversity persistence and key ecosystem services, such as carbon storage. Although the generalization of our findings to other fragmented tropical forests is uncertain, it could negatively affect ecosystem productivity and stability and have broader impacts on coevolved organisms. © 2014 Santos et al.
Keywords: Community Structure; Ecosystem; Forest; Genetic Variability; Landscape; Nonhuman; Phylogeny; Plant Community; Population Abundance; Species Richness; Biodiversity; Classification; Environmental Protection; Forest; Phylogeny; Species Extinction; Tree; Biodiversity; Conservation Of Natural Resources; Extinction, Biological; Forests; Genetic Variation; Phylogeny; Trees